2019
DOI: 10.1016/j.mce.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin and extracellular matrix remodeling: Mechanisms and signaling pathways

Abstract: Fibrosis is associated with accumulation of excess fibrillar collagen, leading to tissue dysfunction. Numerous processes, including inflammation, myofibroblast activation, and endothelial-tomesenchymal transition, play a role in the establishment and progression of fibrosis. Relaxin is a peptide hormone with well-known antifibrotic properties that result from its action on numerous cellular targets to reduce fibrosis. Relaxin activates multiple signal transduction pathways as a mechanism to suppress inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 100 publications
2
29
0
Order By: Relevance
“…Furthermore, it can reduce established scarring by promoting the degradation of aberrant extracellular matrix components. Following on from the review that describes the mechanisms and signaling pathways associated with the extracellular matrix remodeling effects of serelaxin (Ng et al, 2019), this review focuses on newly identified tissue targets of serelaxin therapy in fibrosis, and the limitations associated with (se)relaxin research.…”
mentioning
confidence: 99%
“…Furthermore, it can reduce established scarring by promoting the degradation of aberrant extracellular matrix components. Following on from the review that describes the mechanisms and signaling pathways associated with the extracellular matrix remodeling effects of serelaxin (Ng et al, 2019), this review focuses on newly identified tissue targets of serelaxin therapy in fibrosis, and the limitations associated with (se)relaxin research.…”
mentioning
confidence: 99%
“…Figure 9 shows the results of relaxin signaling pathway analysis. In terms of anti-inflammation, relaxin can inhibit the adhesion of neutrophils to endothelial cells and the infiltration of macrophages, can inhibit the activity of NLRP3 inflammasome and NF- κ B signaling pathway to reduce the inflammatory reaction, and can reduce the levels of cytokines, such as IL-1 β , IL-6, and TNF- α [ 57 ]. For example, relaxin can reduce cardiac inflammatory response by reducing the inflammation mediated by IL-1 β , IL-6, and NLRP3 [ 58 , 59 ] and also can inhibit vascular inflammation by inhibiting the expression of TNF- α and chemokine C-C motif ligand 2 (CCL2) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that relaxin and estrogen can reduce TNF- α and vascular endothelial growth factor by increasing the expression of relaxin family peptide receptor (RXFP1) gene and can increase the expression of anti-inflammatory cytokine IL-10 to improve the symptoms of adjuvant-induced RA in rats [ 61 63 ]. In terms of antifibrosis effect, relaxin can inhibit Smad2 phosphorylation level and fibrosis mediator transforming growth factor- β 1(TGF- β 1) and promote the expression of MMP-1/2/9/13 by activating RXFP1, so as to reduce the production and deposition of collagen to achieve the antifibrosis effect [ 57 ]. Previous studies have found that TGF- β 1 expression was increased in synovium of patients with acute gouty arthritis and in the fibrotic kidney of patients with hyperuricemia [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The top pathways up-regulated by Tbx20KD involved IL-17 and relaxin signaling, as well as transcription misregulation in cancer. IL17 has been shown to regulate the fibrotic response in pro-inflammatory conditions such as psoriasis and pulmonary/liver fibrosis [46][47][48][49], while relaxin has a well-established role in suppressing myofibroblast activation and ECM remodeling [50][51][52].…”
Section: Organ Enriched Transcriptome Is Involved In the Fibrotic Responsementioning
confidence: 99%